PENERAPAN MODEL COOPERATIF LEARNING TIPE MAKE A MATCH UNTUK MENINGKATKAN AKTIVITAS PEMBELAJARAN MATEMATIKA (PTK SISWA KELAS IVA SD NEGERI 81 KOTA BENGKULU) - Habibah, Nur; Ibrahim, Alexon (UNIB Press, 2017)
AbstractThe objective of study was to investigate the effectiveness of theimplementation of Make Match type cooperative learning models to increase the activity of students’ mathematics lessons. The design used was a classroom action research. The subjects were the students of grade IVA SD Negeri 81 Kota Bengkulu in the 2017/2018. Data collection techniques use was direct observation which wased during the process of learning mathematics by using Make a Match learning models. Data analysis techniques were obtained from observations of teacher activities and observations of student activities, the data obtainedfrom observation sheets were described. The results of the study concluded that the application of make-match cooperative learning model could increase student activity in mathematics learning. This can be seen from the teacher and student activity sheets.Keywords: Mathematics, Activity, Cooperative, Make a Match.